THE EFFECT OF RETAIL MIX ON CUNSUMER PURCHASING DECISION (SURVEI ON ALFAMART CUSTOMERS IN KEMILING BANDAR LAMPUNG) - Salsabila, Assyifa; Sugiono, Arif; Aprilia, Hani Damayanti (Jurnal Kompetitif Bisnis, 2022)
This research was aimed to find out the effect of retail mix on consumer purchasing decision on Alfamart Kemiling. The research applies the explanatory with quantitative approach. The population in this study were customer of Alfamart. The sampling technique in this study is non probability sampling with purposive sampling method with sample of 100 respondents. The data were obtained from questionnaire through likert scale. Data analysis using multiple linear regression with used SPSS version 25 program. The result of this study showed variable location, customer service and communication mix has significant effect but variable of product has negative effect on customer purchasing decision.Variable of pricing and store design & display has not effect on consumer purchasing decision.